Forest, Trees, and Woodlands in Africa : An Action Plan for World Bank Engagement - Bromhead, Marjory-Anne (Washington, DC, 2012)
The purpose of this paper is to outline an approach for Bank engagement in forests, trees, and woodlands on farms in Sub-Saharan Africa for the coming five years. The paper takes the framework of the Africa development strategy, which has two main pillars: supporting employment and competitiveness, and building resilience and reducing vulnerability; and one underlying foundation: strengthening capacity and governance. It is consistent with the pillars of the bank forest strategy from 2002, which highlight the contribution of forests to economic development, poverty reduction, and protection of global public goods. Several other World Bank corporate strategies are also relevant for the implementation of this action plan. The primary messages of this paper are linked: enhanced forest, tree and woodland management can play a key role in achieving the goals of the Africa Strategy. Employment generation, improving competitiveness as well as building resilience and reducing vulnerability are the overall objectives of the World Bank's forest engagement in Sub-Saharan Africa; and in many countries the most effective approaches will be outside the traditional forestry institutions and will involve working through operations and reforms supported through other sectors.